Monolithic catalyst, preparation method and application thereof, and method for purifying air

By loading a monolithic catalyst with alumina matrix, manganese oxide and activated carbon on the honeycomb support, the problems of poor economic and operability of formaldehyde removal catalysts in the prior art are solved, and the efficient and long-term formaldehyde purification effect is achieved, which is in line with national safety standards.

CN119909672AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311432308.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing room temperature formaldehyde removal catalyst has poor economicality, complex preparation methods and poor operability. It is not suitable for large-scale use and is difficult to meet the requirements of high reaction activity, long life and efficient purification.

Method used

A honeycomb support is used to carry an alumina matrix, manganese oxide and activated carbon, and is prepared by impregnation method to control the average compound valence of manganese in the range of 3.35-3.95, thereby improving the reactivity and oxidation capacity of the catalyst.

Benefits of technology

It has achieved efficient adsorption and catalytic conversion of formaldehyde in the air, reduced the formaldehyde concentration to 0.08mg/m3, complied with national safety standards, and had a long cycle and stable service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of air pollution control, and discloses a monolithic catalyst, a preparation method and application thereof, and a method for purifying air. The monolithic catalyst comprises a honeycomb carrier as well as an aluminum oxide substrate, manganese oxide and activated carbon which are loaded on the honeycomb carrier, on the basis of the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 55-85 wt%, the content of the alumina matrix is 5-30 wt%, the content of the manganese oxide is 5-35 wt%, and the content of the activated carbon is 3-20 wt%; wherein the average valence of manganese in the monolithic catalyst is 3.35 to 3.95. The monolithic catalyst is applied to air purification, and formaldehyde in air can be efficiently and stably removed for a long period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air pollution control, and in particular to an integral catalyst and a preparation method and application thereof, as well as a method for purifying air. Background Art

[0002] Formaldehyde is the most important type of volatile organic compounds (VOCs). It comes from a wide range of sources, not only from wood materials, floor materials, and paint used in decoration, but also from cosmetics, detergents, incompletely burned tobacco leaves, textile fibers, etc. that are easily overlooked. Formaldehyde is very harmful to the human body. When acute poisoning occurs, symptoms such as burning throat, nausea, fatigue, dyspnea, and pulmonary edema will appear; when chronic poisoning occurs, symptoms such as skin itching, coughing, and chest tightness and shortness of breath will appear; if long-term exposure to low doses of formaldehyde, it will show a decline in the body's immune function, cause neurasthenia, lead to memory loss, and cause chronic respiratory diseases. In severe cases, it will cause blood diseases and induce leukemia. It can be seen that the harm of formaldehyde can no longer be ignored, and its governance has become the focus of people's attention. How to quickly and efficiently reduce the harm of formaldehyde to the human body has become a difficult problem that people urgently need to solve.

[0003] CN105964289A provides a catalyst for removing formaldehyde at room temperature and its preparation method, which loads Ag-Pt on a carrier modified by tetrabutyl titanate to achieve the purpose of removing formaldehyde at room temperature; however, the catalyst provided by this method is economically poor due to the use of precious metals, and does not have the basis for large-scale commercial application. CN107983320A discloses a preparation method and application of a dual-function film for removing formaldehyde, which describes the loading of manganese on an activated carbon carrier modified by rare earth element nitrates, and the preparation of a film with an electrostatic wire solution. The film has both adsorption and catalytic oxidation effects, and can achieve the effect of removing formaldehyde. CN110624403A discloses a filter screen for removing formaldehyde and removing odors, which uses a manganese catalyst obtained by hydrothermal synthesis of a solution containing manganese, iron and oxalate, and then dissolves it in a silicon oxide sol-gel, sprays it on the filter screen and dries it to achieve the function of removing formaldehyde at room temperature.

[0004] However, the room temperature formaldehyde removal catalyst provided by the above patent application is not suitable for large-scale use due to its poor economic efficiency, complicated preparation method and poor operability. In the field of civil room temperature formaldehyde removal, it is necessary to have the following basic characteristics: first, strong formaldehyde removal ability. The national air quality standard requires that the formaldehyde content in the home environment cannot be higher than 0.1 mg / m 3Due to the limitations of the application conditions of room temperature formaldehyde removal catalysts, they are required to have extremely high reaction activity to meet the requirements; secondly, the catalyst strength is high. Room temperature formaldehyde removal agents need to be used in adsorption purification devices in large places such as buildings, office buildings, hospitals, and shopping malls. The air velocity is large, and the catalyst strength must adapt to the impact strength requirements under high air velocity; thirdly, the life is long. Due to mechanism reasons, the formaldehyde removal efficiency of formaldehyde removal agents often decreases as the reaction proceeds, and may even fail completely. Therefore, it is urgent to develop a new type of formaldehyde removal agent to meet the requirements of long-term use. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a monolithic catalyst and its preparation method and application as well as a method for purifying air. The monolithic catalyst of the present invention is applied to air purification and can remove formaldehyde in the air efficiently, over a long period and stably.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a monolithic catalyst, which comprises a honeycomb carrier and an alumina matrix, manganese oxide and activated carbon supported on the honeycomb carrier; based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of the manganese oxide is 5-35% by weight, and the content of the activated carbon is 3-20% by weight;

[0007] Wherein, the average valence of manganese in the integral catalyst is 3.35-3.95.

[0008] A second aspect of the present invention provides a method for preparing a monolithic catalyst, the method comprising the following steps:

[0009] (1) mixing a manganese-based material, an aluminum oxide matrix and a dispersant to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.35-3.95;

[0010] (2) impregnating the honeycomb support into a manganese oxide suspension and an activated carbon suspension by an impregnation method, followed by drying and optionally calcining;

[0011] The amount of manganese-based material, alumina matrix, activated carbon and honeycomb carrier is such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of manganese oxide is 5-35% by weight, and the content of activated carbon is 3-20% by weight.

[0012] The third aspect of the present invention provides a use of the monolithic catalyst described in the first aspect or the monolithic catalyst prepared by the preparation method described in the second aspect in purifying air.

[0013] A fourth aspect of the present invention provides a method for purifying air, the method comprising: contacting air containing formaldehyde with a monolithic catalyst;

[0014] Wherein, the monolithic catalyst is the monolithic catalyst described in the first aspect or the monolithic catalyst prepared by the preparation method described in the second aspect.

[0015] Through the above technical solution, the beneficial effects of the present invention include:

[0016] The monolithic catalyst provided by the present invention is applied to air purification, and the synergistic effect of a specific content of honeycomb carrier-alumina matrix-manganese oxide-activated carbon is utilized, and the average valence of manganese in the monolithic catalyst is controlled within the range of 3.35-3.95, so as to achieve efficient adsorption of formaldehyde in the air, induce strong chemical adsorption of formaldehyde on the catalyst surface and complete catalytic conversion, thereby achieving purification of pollutants such as formaldehyde, and reducing the formaldehyde in the air to 0.08 mg / m 3 The following are in compliance with national safety standards. At the same time, the use of the integral catalyst of the present invention can stably remove formaldehyde from the air over a long period of time.

[0017] The monolithic catalyst preparation method of the present invention is simple, low-cost, high-precision, high-strength, and long-life, and is conducive to industrial promotion. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides a monolithic catalyst, comprising a honeycomb carrier and an alumina matrix, manganese oxide and activated carbon supported on the honeycomb carrier; based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of the manganese oxide is 5-35% by weight, and the content of the activated carbon is 3-20% by weight;

[0020] Wherein, the average valence of manganese in the integral catalyst is 3.35-3.95.

[0021] In the present invention, the average valence of manganese in the monolithic catalyst is 3.35-3.95. Controlling the average valence of manganese in the monolithic catalyst at a relatively high level is beneficial to improving the formaldehyde removal efficiency.

[0022] The average valence AOS of manganese in the present invention is calculated by the following calculation formula:

[0023] AOS = 8.956-1.126×ΔE, ΔE is the difference between the high binding energy and the low binding energy of manganese measured by XPS Mn3S.

[0024] According to the present invention, preferably, based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 60-80% by weight, the content of the alumina matrix is ​​5-25% by weight, the content of manganese oxide is 10-25% by weight, and the content of activated carbon is 5-15% by weight. This preferred embodiment is conducive to improving the adsorption and oxidation capacity of the monolithic catalyst for formaldehyde.

[0025] The content of each component in the monolithic catalyst of the present invention is calculated by the feed amount.

[0026] The sum of the components in the catalyst of the present invention is 100%.

[0027] The monolithic catalyst of the present invention has a special active phase crystal structure, which is beneficial to improving the conversion efficiency of formaldehyde. Preferably, the manganese oxide has α-MnO 2 structure.

[0028] The crystal structure of the manganese oxide described in the present invention is determined by XRD.

[0029] The present invention has no particular limitation on the type of the honeycomb carrier, which can be a conventional choice in the art. Preferably, the honeycomb carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and a metal alloy honeycomb carrier, and more preferably a cordierite honeycomb carrier.

[0030] A second aspect of the present invention provides a method for preparing a monolithic catalyst, the method comprising the following steps:

[0031] (1) mixing a manganese-based material, an aluminum oxide matrix and a dispersant to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.35-3.95;

[0032] (2) impregnating the honeycomb support into a manganese oxide suspension and an activated carbon suspension by an impregnation method, followed by drying and optionally calcining;

[0033] The amount of manganese-based material, alumina matrix, activated carbon and honeycomb carrier is such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of manganese oxide is 5-35% by weight, and the content of activated carbon is 3-20% by weight.

[0034] According to the present invention, preferably, the amount of manganese-based material, alumina matrix, activated carbon and honeycomb carrier is such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the honeycomb carrier is 60-80% by weight, the content of the alumina matrix is ​​5-25% by weight, the content of manganese oxide is 10-25% by weight, and the content of activated carbon is 5-15% by weight.

[0035] According to the present invention, preferably, the specific surface area of ​​the alumina matrix is ​​greater than 100 m 2 / g, preferably 120-250m 2 / g.

[0036] According to the present invention, preferably, the pore volume of the alumina matrix is ​​0.3-1.5 mL / g, preferably 0.5-1 mL / g.

[0037] The use of an alumina matrix having the above characteristics is beneficial to improving the utilization rate of manganese oxide.

[0038] The present invention has no particular limitation on the source of the alumina matrix, which can be purchased commercially or prepared by conventional methods, as long as the above requirements are met.

[0039] According to the present invention, preferably, the specific surface area of ​​the activated carbon is greater than 500m 2 / g, preferably 600-800m 2 / g.

[0040] According to the present invention, preferably, the pore volume of the activated carbon is 0.6-1.5 mL / g, preferably 0.7-1.4 mL / g.

[0041] The use of activated carbon with the above characteristics in combination with manganese oxide is beneficial to improving the efficiency of formaldehyde decomposition.

[0042] According to the present invention, preferably, the method for preparing the manganese-based material comprises the following steps: precipitating the first manganese-containing compound aqueous solution and the second manganese-containing compound aqueous solution, and then crystallizing to obtain the manganese-based material.

[0043] According to the present invention, preferably, the precipitation conditions include: temperature of 30-90° C. and time of 0.3-3 h.

[0044] According to the present invention, preferably, the crystallization conditions include: temperature of 100-150° C. and time of 1-20 h.

[0045] Preferably, the method further comprises: filtering and washing the crystallized product to obtain a manganese-based material.

[0046] The present invention has no particular limitation on the specific methods of filtering and washing, and the filtering and washing can be performed according to conventional methods in the art.

[0047] The present invention has no particular limitation on the number of washing times, and the pH value of the washing agent used for washing is 7.

[0048] According to the present invention, preferably, the first manganese-containing compound is potassium permanganate and / or sodium permanganate.

[0049] According to the present invention, preferably, the second manganese-containing compound is at least one of manganese sulfate, manganese nitrate and manganese acetate.

[0050] In the present invention, the average valence of manganese in the manganese-based material is regulated by reacting a first manganese-containing compound containing high-valent manganese with a second manganese-containing compound containing low-valent manganese.

[0051] According to the present invention, preferably, the concentration of the first manganese compound-containing aqueous solution is 2-15 wt %.

[0052] According to the present invention, preferably, the concentration of the second manganese compound-containing aqueous solution is 30-70 wt %.

[0053] During the preparation of the first manganese compound-containing aqueous solution and the second manganese compound-containing aqueous solution, ultrasound or stirring may be used to mix them uniformly. The same is true for the preparation of the following solutions.

[0054] The present invention has no particular limitation on the amount of the first manganese-containing compound and the second manganese-containing compound, provided that the average valence of manganese in the manganese-based material is within the above range.

[0055] According to the present invention, preferably, in the manganese oxide suspension, D of the manganese-based material 90 The thickness of the coating layer is not greater than 10 micrometers, preferably 1-5 micrometers. With this preferred embodiment, it is easier to form a stable coating layer.

[0056] The present invention has no particular limitation on how to obtain the average particle size of the manganese-based material within the above range, and it can be achieved by conventional technical means, such as grinding.

[0057] According to the present invention, preferably, the mass ratio of the manganese-based material to the dispersant is 1:0.05-0.8, preferably 1:0.1-0.4.

[0058] The present invention has a wide range of selection for the type of the dispersant. Preferably, the dispersant is selected from at least one of polyvinyl alcohol, acrylic acid and methyl acrylate.

[0059] According to the present invention, preferably, the manganese oxide suspension also contains water, and the amount of water used is 30-200 g relative to 1 g of manganese-based material.

[0060] According to the present invention, preferably, the manganese oxide suspension does not contain a surfactant. The surfactant can be a conventional choice in the art, and the present invention will not be described in detail here.

[0061] According to a specific embodiment of the present invention, step (1) comprises: mixing the manganese-based material with a dispersant and an alumina matrix, and then grinding for 1-3 hours to obtain a uniformly mixed manganese oxide suspension.

[0062] According to the present invention, preferably, in the activated carbon suspension, the D 90 No larger than 10 microns, preferably 1-10 microns. In this preferred embodiment, activated carbon with similar size ranges can contact with manganese oxide more fully, and in the reaction, the activated carbon can efficiently adsorb formaldehyde, and the manganese oxide can be efficiently converted, thereby improving the formaldehyde removal rate.

[0063] The present invention has no particular limitation on how to obtain the average particle size of the activated carbon within the above range, and it can be achieved by conventional technical means, such as grinding.

[0064] According to the present invention, preferably, the concentration of the activated carbon suspension is 50-200 g / L.

[0065] Preferably, the activated carbon is dissolved in water to obtain an activated carbon suspension.

[0066] The present invention has no particular limitation on the type of the honeycomb carrier, which can be a conventional choice in the art. Preferably, the honeycomb carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and a metal alloy honeycomb carrier, and more preferably a cordierite honeycomb carrier.

[0067] The present invention has no particular limitation on the size of the honeycomb carrier, and the size can be appropriately selected according to different application sites.

[0068] According to the present invention, preferably, the impregnation method in step (2) comprises: contacting the honeycomb carrier with a manganese oxide suspension, and then drying and calcining to obtain a solid product; contacting the solid product with an activated carbon suspension, and then drying.

[0069] The present invention does not have any particular limitation on the contact temperature of step (2), which can be any temperature that the impregnation liquid can reach. There is no particular limitation on the contact time, as long as the required amount of metal precursor can be loaded on the carrier. In general, the higher the contact temperature and the greater the concentration of the impregnation liquid, the shorter the time required to achieve the same impregnation amount (i.e., the weight difference between the carrier after impregnation and before impregnation); and vice versa. Once the required impregnation amount and conditions are determined, it is easy to select a suitable contact time. The specific operation of the impregnation method is well known to those skilled in the art, and the impregnation method can be a saturated impregnation method or a supersaturated impregnation method. There is no particular limitation on the environment of the impregnation method, and it can be carried out under sealed conditions or in an open environment according to conventional methods in the art, and the lost solvent can be replenished during the contact process or not. Various gases, such as air, nitrogen, water vapor, etc., can be introduced during the contact process, or no new components can be introduced.

[0070] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art. Preferably, the drying conditions include: a temperature of 80-120° C. and a time of 1-5 hours.

[0071] According to the present invention, preferably, the calcination conditions include: a temperature of 300-500° C. and a time of 1-5 hours. This preferred embodiment is beneficial to improving the oxidation capacity of the catalyst.

[0072] The third aspect of the present invention provides a use of the monolithic catalyst described in the first aspect or the monolithic catalyst prepared by the preparation method described in the second aspect in purifying air.

[0073] The monolithic catalyst of the present invention is suitable for purifying one or more volatile organic compounds such as formaldehyde, ozone, VOCs, etc. in the air, and is particularly suitable for purifying formaldehyde in the air.

[0074] A fourth aspect of the present invention provides a method for purifying air, the method comprising: contacting air containing formaldehyde with a monolithic catalyst;

[0075] Wherein, the monolithic catalyst is the monolithic catalyst described in the first aspect or the monolithic catalyst prepared by the preparation method described in the second aspect.

[0076] The monolithic catalyst of the present invention can be used to purify air at low temperature and normal pressure. Preferably, the contact conditions include: temperature of 20-100°C, preferably 25-50°C; volume space velocity of 1000-200000h -1 , preferably 2000-20000h -1 .

[0077] The monolithic catalyst of the present invention is applicable to treating formaldehyde of different concentrations. Preferably, the formaldehyde content in the air is 0.1-100 ppm.

[0078] The integral catalyst of the present invention can be used in different occasions, and can be suitable for purification of indoor air and in-car air, and can also be used as a filter element of an air purifier and a fresh air blower, and is also suitable for use in a high air velocity and low concentration pollutant environment.

[0079] The present invention will be described in detail below through examples.

[0080] In the following examples, the concentrations of carbon monoxide, sulfur dioxide and volatile organic compounds in the tail gas were measured by gas chromatography.

[0081] Example 1

[0082] Preparation of manganese oxide suspension: 3.97g potassium permanganate was dissolved in 32.15g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was mixed with 7.26g of 50 wt% manganese sulfate solution for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.84. The manganese-based material was ground to D using a ball mill. 90 5 microns, and then added polyvinyl alcohol (Shanghai Petrochemical), alumina matrix (specific surface area 165m 2 / g, pore volume 0.56mL / g) and water, wherein the mass ratio of polyvinyl alcohol: manganese-based material: water is 1:10:88, and the ball mill is continued to grind for 2h to obtain a manganese oxide suspension.

[0083] Impregnation with manganese oxide suspension: The cordierite honeycomb carrier is impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 500° C. for 2 hours to obtain a solid product.

[0084] Impregnation of activated carbon suspension: Take activated carbon (specific surface area 650m 2 / g, pore volume 1.1mL / g), placed in water, and ground with a ball mill to D 90 The particle size was 10 microns, and an activated carbon suspension with a concentration of 150 g / L was obtained. The solid product was immersed in the activated carbon suspension for 2 minutes, and then dried at 120° C. for 3 hours to obtain the monolithic catalyst A1. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0085] Example 2

[0086] Preparation of manganese oxide suspension: 3.56g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was then mixed with 6.74g of a 50 wt% manganese sulfate solution for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.84. The manganese-based material was ground to D using a ball mill. 90 5 microns, and then add acrylic acid, aluminum oxide matrix (specific surface area 178m 2 / g, pore volume 0.76mL / g) and water, wherein the mass ratio of acrylic acid: manganese-based material: water is 1:10:88, and the ball mill is continued to grind for 2h to obtain a manganese oxide suspension.

[0087] Impregnation with manganese oxide suspension: The cordierite honeycomb carrier is impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 500° C. for 2 hours to obtain a solid product.

[0088] Impregnation of activated carbon suspension: Take activated carbon (specific surface area 700m 2 / g, pore volume 1.15mL / g), placed in water, and ground with a ball mill to D 90 The particle size of the catalyst is 8 microns, and an activated carbon suspension with a concentration of 150 g / L is obtained. The solid product is immersed in the activated carbon suspension for 2 minutes, and then dried at 120° C. for 3 hours to obtain the monolithic catalyst A2. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0089] Example 3

[0090] Preparation of manganese oxide suspension: 4.02g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, which was mixed with 7.26g of 50 wt% manganese sulfate solution for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.56. The manganese-based material was ground to D using a ball mill. 90 3 microns, and then added polyvinyl alcohol (Shanghai Petrochemical), alumina matrix (specific surface area 102m 2 / g, pore volume 0.41mL / g) and water, wherein the mass ratio of polyvinyl alcohol: manganese-based material: water is 1:10:88, and the ball mill is continued to grind for 2h to obtain a manganese oxide suspension.

[0091] Impregnation with manganese oxide suspension: The cordierite honeycomb carrier is impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 500° C. for 2 hours to obtain a solid product.

[0092] Impregnation of activated carbon suspension: Take activated carbon (specific surface area 650m 2 / g, pore volume 1.1mL / g), placed in water, and ground with a ball mill to D 90 The particle size of the catalyst is 6 microns, and an activated carbon suspension with a concentration of 150 g / L is obtained. The solid product is immersed in the activated carbon suspension for 2 minutes, and then dried at 120° C. for 3 hours to obtain the monolithic catalyst A3. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0093] Example 4

[0094] Preparation of manganese oxide suspension: 6.15g potassium permanganate was dissolved in 40.55g deionized water, heated to 60°C and stirred to dissolve to form a potassium permanganate solution, and 6.14g of 50 wt% manganese sulfate solution was mixed for 3h, and then reacted at 130°C for 18h. The generated brown precipitate was filtered and washed with deionized water for several times until the pH of the washing solution was 7. The filter cake obtained was a manganese-based material. The average valence of manganese in the manganese-based material was 3.92. The manganese-based material was ground to D using a ball mill. 90 5 microns, and then added polyvinyl alcohol (Shanghai Petrochemical), alumina matrix (specific surface area 136m 2 / g, pore volume 0.66mL / g) and water, wherein the mass ratio of polyvinyl alcohol: manganese-based material: water is 1:10:88, and the ball mill is continued to grind for 2h to obtain a manganese oxide suspension.

[0095] Impregnation with manganese oxide suspension: The cordierite honeycomb carrier is impregnated in the manganese oxide suspension for 2 minutes, then dried at 80° C. for 3 hours, and calcined at 500° C. for 2 hours to obtain a solid product.

[0096] Impregnation of activated carbon suspension: Take activated carbon (specific surface area 650m 2 / g, pore volume 1.1mL / g), placed in water, and ground with a ball mill to D 90 The particle size was 10 microns, and an activated carbon suspension with a concentration of 150 g / L was obtained. The solid product was immersed in the activated carbon suspension for 2 minutes, and then dried at 120° C. for 3 hours to obtain the monolithic catalyst A4. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0097] Example 5

[0098] The method of Example 1 was followed, except that the alumina matrix with a specific surface area of ​​90 m 2 / g, pore volume 0.34mL / g.

[0099] The monolithic catalyst A5 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0100] Example 6

[0101] The method of Example 1 was followed, except that the manganese-based material was ground to D during the preparation of the manganese oxide suspension. 90 is 20 microns.

[0102] The monolithic catalyst A6 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0103] Example 7

[0104] The method of Example 1 was followed, except that the activated carbon was ground to D during the preparation of the activated carbon suspension. 90 is 30 microns.

[0105] The monolithic catalyst A7 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0106] Example 8

[0107] The method of Example 1 was followed, except that the activated carbon with a specific surface area of ​​550 m 2 / g, pore volume 0.65mL / g.

[0108] The monolithic catalyst A8 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0109] Comparative Example 1

[0110] The method of Example 1 is followed, except that potassium permanganate is not added, and only manganese sulfate is added, so that the manganese oxide content in the prepared monolithic catalyst is still 16% by weight. Specifically, manganese sulfate is mixed with an aluminum oxide matrix, polyvinyl alcohol, and water to obtain a manganese-containing solution.

[0111] The monolithic catalyst D1 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0112] Comparative Example 2

[0113] The method of Example 1 is followed, except that manganese sulfate is not added, and only potassium permanganate is added, so that the manganese oxide content in the prepared monolithic catalyst is still 16% by weight. Specifically, potassium permanganate is mixed with an aluminum oxide matrix, polyvinyl alcohol, and water to obtain a manganese-containing solution.

[0114] The monolithic catalyst D2 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0115] Comparative Example 3

[0116] The method of Example 1 was followed, except that no activated carbon was added, and the solid product obtained was catalyst D3.

[0117] The monolithic catalyst D3 is obtained. The composition and characteristics of the monolithic catalyst are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] Test Example 1

[0122] This test case includes coating stability test and formaldehyde removal ability test. The coating stability test is measured by ultrasonic method to measure the weight loss before and after 50Hz ultrasound for 30 minutes.

[0123] Formaldehyde removal test: The monolithic catalysts prepared in the examples and comparative examples were weighed and placed in a fixed bed reactor, and then air containing formaldehyde (wherein the formaldehyde concentration was 10 ppm, O 2 21% by volume, the balance being N 2 ) was introduced into a fixed bed reactor and reacted at room temperature and pressure with a volume space velocity of 20000 h -1 After 5 hours of reaction, take samples for analysis and record the formaldehyde concentration in the product. The mixed gas after the reaction is passed into the tail gas absorption tank and can be further processed or discharged after the test meets the environmental protection requirements.

[0124] Table 2

[0125]

[0126]

[0127] Test Example 2

[0128] Formaldehyde removal test: The test was carried out according to the method of test example 1, except that

[0129] Activated carbon particles (30-60 mesh) with a filling mass ratio of 7:93 and the catalyst prepared in Comparative Example 3 were placed in a fixed bed reactor in sequence, and then the air containing formaldehyde passed through the activated carbon first and then through the catalyst prepared in Comparative Example 3. The results are shown in Table 3.

[0130] Table 3

[0131] Example No. <![CDATA[Formaldehyde concentration of product / (mg / m 3 )]]> Test Example 2 2.11

[0132] It can be seen from the results in Table 2-3 that the stability and formaldehyde removal capacity of the integral catalyst coating provided by the present invention are greatly improved, and it has significantly higher purification accuracy when used in formaldehyde purification reactions.

[0133] At the same time, it can be seen from Table 2 that the integral catalyst coating of the present invention has good stability, better catalyst performance and longer service life.

[0134] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A monolithic catalyst, comprising a honeycomb carrier and an alumina matrix, manganese oxide and activated carbon supported on the honeycomb carrier; based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of the manganese oxide is 5-35% by weight, and the content of the activated carbon is 3-20% by weight; in, The average valence of manganese in the monolithic catalyst is 3.35-3.

95.

2. The catalyst according to claim 1, wherein Based on the total weight of the monolithic catalyst, in the monolithic catalyst, the content of the honeycomb carrier is 60-80% by weight, the content of the alumina matrix is ​​5-25% by weight, the content of manganese oxide is 10-25% by weight, and the content of activated carbon is 5-15% by weight; Preferably, the manganese oxide has an α-MnO2 structure.

3. The catalyst according to claim 1 or 2, wherein The honeycomb carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier, an alumina honeycomb carrier and a metal alloy honeycomb carrier, preferably a cordierite honeycomb carrier.

4. A method for preparing a monolithic catalyst, the method comprising the following steps: (1) mixing a manganese-based material, an aluminum oxide matrix and a dispersant to obtain a manganese oxide suspension, wherein the average valence of manganese in the manganese-based material is 3.35-3.95; (2) impregnating the honeycomb support into a manganese oxide suspension and an activated carbon suspension by an impregnation method, followed by drying and optionally calcining; The amount of manganese-based material, alumina matrix, activated carbon and honeycomb carrier is such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the honeycomb carrier is 55-85% by weight, the content of the alumina matrix is ​​5-30% by weight, the content of manganese oxide is 5-35% by weight, and the content of activated carbon is 3-20% by weight.

5. The method according to claim 4, wherein: The amount of manganese-based material, alumina matrix, activated carbon and honeycomb carrier is such that in the prepared monolithic catalyst, based on the total weight of the monolithic catalyst, the content of the honeycomb carrier is 60-80% by weight, the content of the alumina matrix is ​​5-25% by weight, the content of manganese oxide is 10-25% by weight, and the content of activated carbon is 5-15% by weight.

6. The method according to claim 4, wherein: The specific surface area of ​​the alumina matrix is ​​greater than 100 m 2 / g, preferably 120-250m 2 / g; the pore volume is 0.3-1.5mL / g, preferably 0.5-1mL / g; Preferably, the specific surface area of ​​the activated carbon is greater than 500 m 2 / g, preferably 600-800m 2 / g; the pore volume is 0.6-1.5mL / g, preferably 0.7-1.4mL / g.

7. The method according to any one of claims 4 to 6, wherein: The method for preparing the manganese-based material comprises the following steps: precipitating a first manganese-containing compound aqueous solution and a second manganese-containing compound aqueous solution, and then crystallizing to obtain a manganese-based material; Preferably, the precipitation conditions include: temperature of 30-90°C and time of 0.3-3h; Preferably, the crystallization conditions include: temperature of 100-150°C and time of 1-20h; Preferably, the first manganese-containing compound is potassium permanganate and / or sodium permanganate; Preferably, the concentration of the first manganese-containing compound aqueous solution is 2-15 wt %; Preferably, the second manganese-containing compound is at least one of manganese sulfate, manganese nitrate and manganese acetate; Preferably, the concentration of the second manganese compound-containing aqueous solution is 30-70 wt %.

8. The method according to any one of claims 4 to 7, wherein: In the manganese oxide suspension, the D 90 Not more than 10 microns, preferably 1-5 microns; Preferably, the mass ratio of the manganese-based material to the dispersant is 1:0.05-0.8, preferably 1:0.1-0.4; Preferably, the dispersant is selected from at least one of polyvinyl alcohol, acrylic acid and methyl acrylate; Preferably, the manganese oxide suspension does not contain a surfactant.

9. The method according to any one of claims 4 to 8, wherein: In the activated carbon suspension, the D 90 Not more than 10 microns, preferably 1-10 microns; Preferably, the concentration of the activated carbon suspension is 50-200 g / L; Preferably, the honeycomb carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and a metal alloy honeycomb carrier, preferably a cordierite honeycomb carrier.

10. The method according to any one of claims 4 to 9, wherein: The impregnation method in step (2) comprises: contacting the honeycomb carrier with a manganese oxide suspension, and then drying and calcining to obtain a solid product; contacting the solid product with an activated carbon suspension, and then drying; Preferably, the calcination conditions include: temperature of 300-500° C. and time of 1-5 h.

11. Use of the monolithic catalyst according to any one of claims 1 to 3 or the monolithic catalyst prepared by the preparation method according to any one of claims 4 to 10 in purifying air, preferably in purifying formaldehyde in air.

12. A method for purifying air, the method comprising: contacting the formaldehyde-containing air with the monolithic catalyst; Wherein, the monolithic catalyst is the monolithic catalyst described in any one of claims 1 to 3 or the monolithic catalyst prepared by the preparation method described in any one of claims 4 to 10; Preferably, the contact conditions include: temperature of 20-100°C, preferably 20-50°C; volume space velocity of 1000-200000h -1 , preferably 2000-20000h -1 ; Preferably, the formaldehyde content in the air is 0.1-10 ppm.

Citation Information

Patent Citations

  • Catalyst for removing formaldehyde at room temperature, and preparation method of catalyst

    CN105964289A

  • Preparation method of double-function film for removing formaldehyde as well as product and application thereof

    CN107983320A

  • Filter screen capable of removing formaldehyde and peculiar smell, and preparation and application thereof

    CN110624403A

  • Granular non-noble-metal efficient integrated air purification composite material

    CN105833842A

  • Manganese oxide catalyst, integral catalyst containing manganese oxide and application thereof

    CN107519860A